STUDENTS’ ERRORS IN WRITING SIMPLE PRESENT TENSE AT COUNSELING DEPARTMENT OF ACHMAD YANI UNIVERSITY - Helmi (Universitas Achmad Yani Banjarmasin, 2021)
Students’ Errors in Writing Simple Present Tense at Counseling Department of Achmad Yani University. The objective of this study is to analyze the students’ errors in writing sentences in simple present tense. The scope of the research is focused on one tenses namely simple present tense. Research method was used in this research is descriptive qualitative. Based on the result of the research, the researcher could conclude that most of subject or sample of the research did mistakes in misinformation because they write wrong in grammatical form and made the sentences were incorrect